2007
DOI: 10.5650/jos.56.283
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Medium- and Long-chain Triacylglycerols Accelerate Diet-Induced Thermogenesis in Humans

Abstract: This study investigated the effects of a liquid meal containing medium-and long-chain triacylglycerols (MLCT) on diet-induced thermogenesis (DIT) and was conducted in double-blind crossover manner. Twenty subjects participated in this examination. The subjects consumed the liquid meal, which was made with 14g of canola oil (LCT, long-chain triacylglycerols) or MLCT containing about 12% medium-chain fatty acids (MCFA). Oxygen consumption and carbon dioxide production were measured by indirect calorimetry. Resti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 14 publications
0
42
0
1
Order By: Relevance
“…Kasai et al (2003b) reported that subjects consumed the test bread, made with 14 g (about 6% of total energy) of MLCT containing 1.7 g MCFAs, and had a significant reduction in body weight and body fat accumulation. Similar researches were often seen recently (Nosaka et al, 2003;Ogawa et al, 2007). In our research, subjects were asked to consume 25-30 g MLCT oil daily, which contains about 13% MCFAs ( Table 2).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Kasai et al (2003b) reported that subjects consumed the test bread, made with 14 g (about 6% of total energy) of MLCT containing 1.7 g MCFAs, and had a significant reduction in body weight and body fat accumulation. Similar researches were often seen recently (Nosaka et al, 2003;Ogawa et al, 2007). In our research, subjects were asked to consume 25-30 g MLCT oil daily, which contains about 13% MCFAs ( Table 2).…”
Section: Discussionmentioning
confidence: 54%
“…Reduction of body weight and body fat weight by consumption of MCT relative to LCT is attributed to increased energy expenditure and fat oxidation, respectively (St-Onge et al, 2003a, b;Ogawa et al, 2007), but the energy expenditure and fat oxidation were to a lower extent in individuals of greater body weight compared with individuals of lower body weight (St-Onge and Jones, 2003). This implies that subjects with greater BMI or body weight might not respond better to MCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4) Dietinduced thermogenesis is accelerated as a result. 5) Many investigations during the past few years have reported that the intake of MCFA or MCT resulted in less body weight gain and body fat mass in animals and humans. [6][7][8][9] Our previous studies on humans have suggested that dietary oil containing MCFA could reduce in hypertriglyceridemic subjects the body weight, body mass index (BMI), body fat mass, waist circumference (WC), hip circumference (HC) and waist-hip ratio when compared to oil containing LCFA, and that these effects were much better in subjects who were male, overweight and less than 60 years old.…”
mentioning
confidence: 99%
“…6) Recently, another kind of fatty acids, MCFAs have become more attractive because they have been found to be effective in the reduction of body weight and body fat weight in both humans, and animals. [7][8][9][10][11][12][13][14][15][16] As for effects of MCFAs on blood TG in humans, there are contradictory reports. Some investigations have found negative effects of MCFAs on blood TG.…”
mentioning
confidence: 99%